Evaluating user influence in Twitter based on hashtags using data mining - Neha, Maheen Absar; Rahman, Md. Intisher; Nuzhat, Mahpara; Zereen, Sifat (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.